2017
DOI: 10.1103/physrevd.95.046007
|View full text |Cite
|
Sign up to set email alerts
|

Deformed relativity symmetries and the local structure of spacetime

Abstract: A spacetime interpretation of deformed relativity symmetry groups was recently proposed by resorting to Finslerian geometries, seen as the outcome of a continuous limit endowed with first order corrections from the quantum gravity regime. In this work we further investigate such connection between deformed algebras and Finslerian geometries by showing that the Finsler geometries associated to the generalisation of the Poincar\'{e} group (the so called $\kappa$-Poincar\'{e} Hopf algebra) are maximally symmetric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 40 publications
(84 reference statements)
0
46
0
Order By: Relevance
“…ǫ = 0, F ǫ is a 1-homogeneous Finsler function, for massless particles F 0 must not necessarily be 1-homogeneous. The transition from a dispersion relation to a Finslerian geometry has been worked out explicitly for Planck scale modified dispersion relations [2,38] and for weakly premetric electrodynamics [25]. Depending on the Hamiltonian from which one starts a huge variety of Finsler functions can be obtained.…”
Section: A Duals Of Dispersion Relationsmentioning
confidence: 99%
“…ǫ = 0, F ǫ is a 1-homogeneous Finsler function, for massless particles F 0 must not necessarily be 1-homogeneous. The transition from a dispersion relation to a Finslerian geometry has been worked out explicitly for Planck scale modified dispersion relations [2,38] and for weakly premetric electrodynamics [25]. Depending on the Hamiltonian from which one starts a huge variety of Finsler functions can be obtained.…”
Section: A Duals Of Dispersion Relationsmentioning
confidence: 99%
“…In the DSR framework, Finsler spacetimes have been studied for flat spacetime [32,33], and also for curved spacetimes [34]. In those papers it was shown that a deformed dispersion relation produce a velocity dependence on the metric.…”
Section: Introductionmentioning
confidence: 99%
“…Examples are premetric electrodynamics [11] describing among other systems the electromagnetic field in crystals [12] or wave equations in solids [13] which can be used to model earthquake waves [14]. Moreover MDRs are used as an effective description of quantum gravity effects [15][16][17][18], making spacetime effectively a medium whose origin lies in the four momentum dependent scattering of elementary particles with the graviton. More fundamentally MDRs emerge from field theories which break local Lorentz invariance [19], as studied in the standard model extension [20], very special and very general relativity [21][22][23] or again in premetric resp.…”
Section: Introductionmentioning
confidence: 99%